Development of a theoretical construct for teacher expertise in the Chinese context and identification of its components: A mixed-methods study - Cai, Yonghong; Li, Yanli; Tang, Runjia (Frontiers in Psychology, 2023)
Teacher expertise is a vital element of teaching quality. This mixed-method study develops a theoretical construct for teacher expertise in the Chinese context and identifies its components. Critical incident interviews with 102 primary and secondary school teachers were conducted to develop a construct for teacher expertise and explore its components. To verify the construct validity and discriminant validity, a survey of 1,041 teachers was conducted in 21 primary schools and 20 secondary schools in Hebei and Shanxi provinces (one city in each province, respectively). A grounded theory analysis of 621 stories from critical incident interviews resulted in a coding scheme with three code dimensions: knowledge structure, teaching ability, and professional development agency. Confirmative factor analysis and independent sample t-tests indicated that these had good construct validity and discriminant validity. This construct for teacher expertise can be used to differentiate expert teachers from experienced and novice teachers in terms of their levels of teaching ability and professional development agency. This study expands on prior studies and complements recent theoretical models describing teacher expertise and should also be useful for informing teacher educators on how to train and assess teachers.